The unseen face of humanitarian crisis in Eastern Democratic Republic of Congo: was nutritional relief properly targeted?. Issue 1 (1st January 2000) - Porignon, Denis; Katulanya, Isu; Elongo, Lokombe; Ntalemwa, Nytha; Tonglet, René; Dramaix, Michèle; Hennart, Philippe
Abstract : STUDY OBJECTIVE: Comparison of children's nutritional status in refugee populations with that of local host populations, one year after outbreak refugee crisis in the North Kivu region of Democratic Republic of Congo. DESIGN: Cross sectional surveys. SETTING: Temporary and other settlements, in the town of Goma and surrounding rural areas. SUBJECTS: Anthropometric indicators of nutritional status and presence or absence of oedema were measured among 5121 children aged 6 to 59 months recruited by cluster sampling with probability proportional to size, between June and August 1995. RESULTS: Children in all locations demonstrated a typical pattern of growth deficit relative to international reference. Prevalence of acute malnutrition (wt/ht < −2 Z score) was higher among children in the rural non-refugee populations (3.8 and 5.8%) than among those in the urban non-refugee populations (1.4%) or in the refugee population living in temporary settlements (1.7%). Presence of oedema was scarcely noticed in camps (0.4%) while it was a common observation at least in the most remote rural areas (10.1%). As compared with baseline data collected in 1989, there is evidence that nutritional status was worsening in rural non-refugee populations. CONCLUSIONS: Children living in the main town or in the refugee camps benefited the most from nutritional relief while those in the rural non-refugee areas were ignored. This is a worrying case of inequity in nutritional relief.